The Effect of the Wordwall Educational Game on Madurese Language Learning Outcomes of Fifth Grade Students at UPTD SDN Tanjung Jati 2 - Yuniar, Faridatul; Fauziyah, Humairah (Widyagogik, 2025)
This study was motivated by the low learning outcomes of students in the Madurese language, particularly in mastering vocabulary and understanding narrative texts. The purpose of this study was to determine the effect of the Wordwall educational game on the Madurese learning outcomes of fifth-grade students at UPTD SDN Tanjung Jati 2. This study applied a quantitative approach with a one-group pretest-posttest design. The research subjects consisted of 18 fifth-grade students. Data were collected through tests (pretest and posttest) and observation sheets of learning implementation. The hypothesis was tested using the Wilcoxon Signed Rank Test, which obtained a significance value of 0.001 0.05, indicating that the alternative hypothesis was accepted. The results showed that the use of Wordwall had a significant effect on students' Madurese learning outcomes. The media proved to be effective in improving learning outcomes as well as creating a more interactive, enjoyable, and engaging classroom atmosphere.